2004
DOI: 10.1074/jbc.m311905200
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyltranspeptidase Stimulates Receptor Activator of Nuclear Factor-κB Ligand Expression Independent of Its Enzymatic Activity and Serves as a Pathological Bone-resorbing Factor

Abstract: A novel bone-resorbing factor was cloned using an expression cloning technique, which involved a Xenopus oocyte expression system and an assay for osteoclast formation. A candidate clone was isolated from a BW5147 mouse T-lymphoma cell cDNA library. Sequencing analysis identified the factor as ␥-glutamyltranspeptidase (GGT), which is an enzyme involved in glutathione metabolism. The addition of purified GGT protein to mouse bone marrow culture effectively induced formation of osteoclasts. An antibody against G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 36 publications
6
66
1
Order By: Relevance
“…A large longitudinal study (16,036 Korean men aged ≥ 50 years) demonstrated that a higher serum GGT level was associated with increased development of osteoporotic fractures over a mean 3-year follow-up period [50]. Experimental data indicate that both a deficiency and an excess of GGT result in osteoporosis [49,[51][52][53]. GGT in vitro stimulates osteoclast formation (independently of its enzymatic activity) and expression of receptor activator of nuclear factor-kB ligand (RANKL) mRNA and protein from bone marrow stromal cells, and in transgenic mice promotes osteoporosis [51][52][53].…”
Section: Liver-bone Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large longitudinal study (16,036 Korean men aged ≥ 50 years) demonstrated that a higher serum GGT level was associated with increased development of osteoporotic fractures over a mean 3-year follow-up period [50]. Experimental data indicate that both a deficiency and an excess of GGT result in osteoporosis [49,[51][52][53]. GGT in vitro stimulates osteoclast formation (independently of its enzymatic activity) and expression of receptor activator of nuclear factor-kB ligand (RANKL) mRNA and protein from bone marrow stromal cells, and in transgenic mice promotes osteoporosis [51][52][53].…”
Section: Liver-bone Interactionsmentioning
confidence: 99%
“…Experimental data indicate that both a deficiency and an excess of GGT result in osteoporosis [49,[51][52][53]. GGT in vitro stimulates osteoclast formation (independently of its enzymatic activity) and expression of receptor activator of nuclear factor-kB ligand (RANKL) mRNA and protein from bone marrow stromal cells, and in transgenic mice promotes osteoporosis [51][52][53]. It has been proposed that osteopenia/osteoporosis in GGT-deficient (GGT-/+) mice is caused by suppression of bone formation, while excess of GGT results mainly in acceleration of bone resorption [53].…”
Section: Liver-bone Interactionsmentioning
confidence: 99%
“…Gamma glutamyl transferase 1 GGT1 GGT1 is a potential marker for bone resorption. It acts as a pathological bone resorbing factor by stimulating RANK ligand (Asaba et al, 2006;Niida et al, 2004). A disintegrin and metallopeptidase domain 12 ADAM12 Stimulates bone growth in mice by modulating chondrocyte proliferation and maturation through mechanisms probably involving both metalloproteinase and adhesion activities (Kveiborg et al, 2006).…”
Section: Ppargmentioning
confidence: 99%
“…First, GGT may directly play a pathogenic role in the onset of metabolic bone diseases. A previous in vitro study has shown that GGT stimulates receptor activator of nuclear factor-kappaB ligand expression and effectively induces the formation of osteoclasts, independent of its enzymatic activity [14]. Furthermore, the overexpression of GGT in transgenic mice has been reported to accelerate bone resorption and cause osteoporosis [15].…”
Section: Discussionmentioning
confidence: 99%